Water Quality Assessment of Derinçay Stream (Çorum) by Biotic Indices - Faruk Maraşlıoğlu; Süleyman İpek (Aquatic Sciences and Engineering)
In this study, counting and identification were performed on epiphytic diatom samples taken from 6 sampling stations located on the Derinçay Stream (Çorum). In the study, 42 taxa belonging to Bacillariophyta were identified, and the dominant taxon of the stream was Nitschia palea. According to some biotic indices such as the Trophic Diatom Index (TDI) and Saprobic Index (SI), it was determined that the Derinçay Stream has a hypertrophic trophic structure corresponding to the "bad" ecological status with an average TDI value of 79.8, and according to the SI, the upper stations (St1, St2) were organically slightly polluted corresponding to β-mesosaprobic, while the other stations were determined to be heavily polluted corresponding to α-mesosaprobic. When looking at the similarities of the stations, the stations with the highest similarity values were the 4th and 6th stations, while the similarity of the 1st and 6th stations was low. When Shannon diversity index (H’) averages are examined, the stream is classified as "low diversity" and "heavily polluted". According to the Pielou evenness index (J’), the community balance at the epiphytic flora stations was better in other months, except February 2021. According to Margalef's species richness index (d), species richness decreases upstream from downstream. When the data in the study area are evaluated, it was seen that the stream is under the threat of pollution, and the SI results represented the ecological structure of the stream better than the TDI results.